2018
DOI: 10.1016/s2352-4642(17)30181-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a renal angina index for prediction of severe acute kidney injury in critically ill children: a multicentre, multinational, prospective observational study

Abstract: Earlier, better prediction of severe AKI has the potential to improve AKI associated patient outcomes. Compared to isolated, context-free changes in SCr, renal angina risk assessment improved accuracy for prediction of severe AKI in critically ill children and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 23 publications
7
90
0
Order By: Relevance
“…The PARI does not have an extremely high PPV and cannot be expected to detect those patients at higher risk of persistent AKI. However, renal angina aims to screen patients at risk of subsequent persistent AKI, and it is enough that the scoring has a high NPV, similar to the previous studies 9,10 . The PARI, in our analysis, also has a high NPV and is expected to exclude the low risk of persistent AKI (about 87.5% occupied in ICU) and to identify those at potentially high risk of persistent AKI (about 12.5% occupied in ICU).…”
Section: Discussionmentioning
confidence: 73%
“…The PARI does not have an extremely high PPV and cannot be expected to detect those patients at higher risk of persistent AKI. However, renal angina aims to screen patients at risk of subsequent persistent AKI, and it is enough that the scoring has a high NPV, similar to the previous studies 9,10 . The PARI, in our analysis, also has a high NPV and is expected to exclude the low risk of persistent AKI (about 87.5% occupied in ICU) and to identify those at potentially high risk of persistent AKI (about 12.5% occupied in ICU).…”
Section: Discussionmentioning
confidence: 73%
“…We recommend the use of clinical scoring systems to predict AKI post-injury or when the timing of injury is unknown. The Renal Angina Index (RAI) has emerged as a useful scoring system in children who are critically ill (25). The RAI combines validated clinical risk factors (ICU admission, solid organ or stem cell transplant, mechanical ventilation, and vasopressor need) with evidence for decreased kidney function (increases in serum creatinine or degrees of fluid accumulation) to stratify patients at risk for subsequent severe AKI.…”
Section: Identify Patients Who Are At Risk For Aki Post-injury Earlymentioning
confidence: 99%
“…In critically ill children, Basu et al [92] combined risk criteria (solid organ or stem-cell transplantation, mechanical ventilation, or vasoactive drug support) and injury criteria (change in serum creatinine relative to baseline or fluid overload percentage) assessed 12 h after ICU admission into a score named the renal angina index (RAI). They showed that a RAI ≥8 was independently associated with the occurrence of severe AKI at 72 h. In critically ill adults, Malhotra et al [93] developed a risk score including 10 clinical parameters for the prediction of AKI in the first 7 days.…”
Section: Acute Kidney Injury and Critical Care Nephrologymentioning
confidence: 99%
“…Importantly, renoprotective recommendations such as avoidance of nephrotoxic drugs and hyperglycemia, as well as optimization of the hemodynamic status (KDIGO bundle) [102], can prevent AKI in high-risk groups. This was demonstrated in the PrevAKI trial [92], in which patients undergoing cardiac surgery with TIMP2 × IGFBP7 > 0.3 (measured 4 h after cardiopulmonary bypass) were randomized to receive the KDIGO bundle versus standard of care. The investigators showed a significant decrease in the incidence of postoperative AKI when the KDIGO bundle was implemented.…”
Section: Acute Kidney Injury and Critical Care Nephrologymentioning
confidence: 99%